A New Approach Against Some Oral Pathogenic Bacteria Using a Chimeric Antimicrobial Peptide Derived from the Camel Milk; Lactoferrampin - Lactoferricin Chimer - Mohammadipour, Hamideh S.; Akbari, Majid; Tanhaeian, Abbas; Pourgonabadi, Solmaz; Sekandari, Salehe; Karimian, Elnaz (Current Drug Discovery Technologies, 2021)
Objectives: The present study was conducted to evaluate the antimicrobial effects of the recombinant chimer present in the lactoferrampin-lactoferricin [LFA-LFC] derived from the camel milk on some oral bacteria responsible for dental caries and endodontic failures. Methods and Material: The antimicrobial activity was assessed on the Streptococcus mutans [ATCC 35668], Streptococcus salivarius [ATCC 9222], Streptococcus oralis [ATCC 35037], and Enterococcus faecalis [ATCC 29212], using the microbroth dilution method. The cytotoxicity analysis was done through the MTT method on the human gingival fibroblasts. The data were reported using the descriptive methods and were analyzed by the one-way analysis of variance (ANOVA) and Tukey HSD test. Results: Results showed that the chimeric peptide had the highest bacteriostatic effect on S. salivarius with the lowest minimum inhibitory concentration value of 1.22 μg/Ml. Also, LFA-LFC chimer was more effective against S. mutans and S. salivarius compared to using 0.2% chlorhexidine mouthwash. The minimum bactericidal concentration analysis showed the most bactericidal effect against S. mutans [1.256 μg/mL]. In spite of the greater antibacterial effect on the evaluated streptococci, this peptide showed lower bacteriostatic and bactericidal properties against E. faecalis compared to the chlorhexidine. Based on cytotoxicity assay, over 50% of the cells were viable in all the evaluation times, demonstrating the biocompatibility of the peptide. Conclusion: The LFA-LFC chimer revealed comparable or even more effective antibacterial properties compared to the chlorhexidine mouthwash against the caries-inducing bacteria with no toxicity on the human gingival fibroblast cells. So, this peptide can be used as a safe alternative to chlorhexidine and other chemicals in dental applications for the prevention and management of dental caries.
Keywords: oral pathogenic bacteria